2021
DOI: 10.3201/eid2702.202143
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium ovale wallikeri and P. ovale curtisi Infections and Diagnostic Approaches to Imported Malaria, France, 2013–2018

Abstract: Patients infected with P. ovale wallikeri displayed deeper thrombocytopenia and a shorter latency period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 40 publications
0
34
0
3
Order By: Relevance
“…It is widely distributed in sub-Saharan Africa with overlapping presence with P. falciparum [46,47]. P. ovale, also endemic in Africa, where it probably represents the main agent of relapsing malaria, had a prevalence of 6.47% falling within the reported range [48][49][50][51][52]. P. vivax was identified in mixed infections with P. falciparum (three cases) and as a single infection (one case) in patients arriving from Africa.…”
Section: Discussionmentioning
confidence: 96%
“…It is widely distributed in sub-Saharan Africa with overlapping presence with P. falciparum [46,47]. P. ovale, also endemic in Africa, where it probably represents the main agent of relapsing malaria, had a prevalence of 6.47% falling within the reported range [48][49][50][51][52]. P. vivax was identified in mixed infections with P. falciparum (three cases) and as a single infection (one case) in patients arriving from Africa.…”
Section: Discussionmentioning
confidence: 96%
“…Aldolase-RDT (47.8%) showed a higher sensitivity than pLDH-RDT (10.6%) for both species. In addition, two different RDT showed different sensitivity to detect Pow, i.e., 50% and 16% compared to 45.5% and 4.2% for Poc for Aldolase-RDT and pLDH-RDT, respectively; however, the difference was not significant for Aldolase-RDT [32]. The higher pLDH-RDT positivity with Pow may be explained by its ability to produce a higher amount of LDH compared to Poc [20].…”
Section: Rapid Diagnostic Testsmentioning
confidence: 89%
“…A recent study from France reported 677 P. ovale spp. imported cases (309 Poc and 368 Pow) and suggested a difference in sensitivity of the two species depending on the RDT type used for diagnosis [32]. Aldolase-RDT (47.8%) showed a higher sensitivity than pLDH-RDT (10.6%) for both species.…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Plasmodium ovale wallikeri displays a shorter latency period (time to onset of symptoms, linked to the dormant liver hypnozoite life-cycle stages) and deeper thrombocytopaenia (low blood platelet levels) than Plasmodium ovale curtisi [42][43][44][45]. In addition, where malaria transmission is seasonal, as it is in much of West Africa, latency periods are significantly lower during transmission season [42,43]. Plasmodium knowlesi, which naturally infects macaques but can be transmitted to humans, is found across southeast Asia following the distribution of its macaque hosts.…”
Section: Expanding Horizons: Sequencing Across the Genus Plasmodiummentioning
confidence: 99%